Effect of cigarette smoking and physical activity on the severity of primary angle closure glaucoma in Malay patients - Seong, Niven Teh Chong (2017)
INTRODUCTION Glaucoma is the leading cause of irreversible blindness worldwide, with Asians accounting for approximately half of the world’s glaucoma cases. Primary Open Angle Glaucoma is the most common form of glaucoma but Primary Angle Closure Glaucoma (PACG) constitute a higher number of cases in Asia. Progression of glaucoma is common; despite good control of intraocular pressure (IOP). Risk factors associated with progression of glaucoma can be nonmodifiable or modifiable. Research on identification of modifiable risk factors are scarce. Modifiable risk factors include cigarette smoking and physical activity. There are limited evidences on the potential association between cigarette smoking and physical activities on the development, progression, and severity of PACG. OBJECTIVE To determine the association between cigarette smoking and physical activity on the severity of primary angle closure glaucoma (PACG) in Malay patients. METHODOLOGY A cross-sectional study was conducted between April 2014 and August 2016 involving five ophthalmology clinics in Malaysia: Hospital Universiti Sains Malaysia (HUSM), Hospital Raja Perempuan Zainab II (HRPZ II), Hospital Kuala Lumpur (HKL), Hospital Sultanah Bahiyah (HSB) and Hospital Sultanah Nur Zahirah (HSNZ). Only Malay patients who were able to provide two consecutive reliable and reproducible Humphrey Visual Field (HVF) 24-2 analyses were included. Severity of glaucoma was based on modified Advanced GlaucomaIntervention Study (AGIS) scoring system on HVF and categorised into mild, moderate and severe glaucoma. Face to face interview was conducted to assess their smoking habits and physical activities. Their smoking status was obtained using validated questionnaires from Singapore Malay Eye Study (SiMES). Cigarette smoking was divided into active smoker, ex-smoker, passive smoker and non-smoker. Duration of smoking and number of cigarette smoked per day was documented. Physical activity status was assessed using validated Bahasa Malaysia version of International Physical Activity Questionnaire (IPAQ). Based on their physical activities over the past 7 days, PACG patients was categorised into mild, moderate and heavy physical activity. The duration of physical activity and measurement of energy requirement (METs) was also calculated. Univariate analysis was conducted to examine other risk factors for severity of glaucoma and AGIS score. The association of smoking and physical activity with AGIS score was analysed using multiple linear regression (MLR). RESULTS A total of 150 Malay patients were recruited (50 with mild, 50 with moderate and 50 with severe glaucoma). There was significant association between cigarette smoking and severity of glaucoma (p = 0.038). A significant association was also seen between the number of cigarette smoked and severity of glaucoma (p = 0.044). However, there was no significant association in duration of smoking (in years) with severity of glaucoma. Smoking do not appear to increase the AGIS score significantly but every increase in number of cigarette smoked increases the AGIS score by 0.7 (adjusted b 0.65, 95% CI 0.27, 1.03, p = 0.001). There was significant inverse relationship between physical activity and AGIS score. Every increase in physical activity reduces the AGIS score by 3.4 (adjusted b -3.41, 95% CI -5.23, - 1.59, p < 0.001). CONCLUSION Cigarette smoking and physical activity are potential modifiable risk factor for severity of PACG. Cessation of cigarette smoking may help in halting the progression of glaucomatous visual field defect. Physical activity may protect against having more severe glaucoma. It is recommended that PACG patients practice healthier lifestyle to prevent progression of PACG.